Conciencia fonológica y decodificación lectora en estudiantes (primer grado, primaria) de una institución educativa - Callao Cercado - Baldassari Arias, Lourdes María (2010)
The present investigation aimed to assess the relationship between phonological awareness and reading decoding. The sample consisted of 133 elementary first grader students from a school located in Callao. The phonological awareness was measured by the Phonological Awareness Test whose authors are José Luis Sánchez Ramos and Isabel Cuadrado Gordillo, meanwhile the reading decoding was specifically measured by Screening Test for Dyslexia whose authors are Mabel Condemarín and Blomquist. By processing the data it was found that most students of evaluated sample showed a middle reading decoding level and had middle level in phonological awareness. While performing the correlation analysis it was found a significant relationship between phonological awareness and reading decoding. As for the correlation between the dimensions of phonological awareness (syllable level and the phonemic level) and reading decoding also it was found a significant relationship.